Signifikansi Ekumenisme Dalam Perspektif Teologis Katolik - Antonius Denny Firmanto (Seri Filsafat Teologi, 2023)
Ecclesiology discusses the identity, essence of existence, and function of the Church concerning the identity and mission of the Church in the world. It explored aspects of the experience of the Christian community as a framework for interpreting the experience of faith. Conflicts on interpretations and applications of the Scripture’s messages about justification by faith in the sixteenth century were the cause of the doctrinal divisions and conflicts between the Lutheran Confession and the Roman Catholic Church’s Council of Trent. This study exploited a qualitative research method by exploring literature. By improving recent studies of Scripture and referring to the history of theology and dogma, the ecumenical dialogue after the Second Vatican Council resulted in renewed opinion towards ecumenical unity. Ecumenism means a religious initiative towards the oneness of the Church. It increased cooperation and better understanding between groups within Christianity or church denominations. The study results showed that the Roman Catholic Church had various views on the existence of churches. The context of the times, the dominant thoughts of the time, and the meaning of the Christian faith were the main contributors that gave birth to this diversity.